The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1600-0420.2007.00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluid dynamics in three 25‐gauge vitrectomy systems: principles for use in vitreoretinal surgery

Abstract: IntroductionSutureless 25-gauge pars plana vitrectomy has the potential to reduce the length of surgery and postoperative inflammation at the sclerotomy sites, thus decreasing patient discomfort postoperatively and hastening recovery (Chen 1996;Kwok et al. 1999;Jackson 2000;Lam et al. 2000;Rahman et al. 2000;Fujii et al. 2002a).This technology for vitrectomy, first described by De Juan & Hickingbotham (1990), has changed to facilitate transconjunctival sutureless vitrectomy (Fujii et al. 2002b). Smaller instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…3,15,17 In contrast, the vitreous flow rates showed an increasing trend for all gauges tested, comparing 1,000 CPM and 5,000 CPM with a maximum peak at 5,000 CPM for all gauges. Vitreous is classified as a gelatinous fluid, made up of 98% liquid and 2% protein, 3,18 containing chunks that can obstruct ANALYSIS OF ULTRAHIGH-SPEED VITREOUS CUTTERS RIBEIRO ET AL the cutter port and increase the resistance of the flow inside the aspiration tubing. As the cut rate increases at the same aspiration level, the vitreous chunks that are being cut become smaller and less resistant to aspiration, a feature that becomes more significant the smaller the gauge of the instrument.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,15,17 In contrast, the vitreous flow rates showed an increasing trend for all gauges tested, comparing 1,000 CPM and 5,000 CPM with a maximum peak at 5,000 CPM for all gauges. Vitreous is classified as a gelatinous fluid, made up of 98% liquid and 2% protein, 3,18 containing chunks that can obstruct ANALYSIS OF ULTRAHIGH-SPEED VITREOUS CUTTERS RIBEIRO ET AL the cutter port and increase the resistance of the flow inside the aspiration tubing. As the cut rate increases at the same aspiration level, the vitreous chunks that are being cut become smaller and less resistant to aspiration, a feature that becomes more significant the smaller the gauge of the instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Our methods have been described in detail elsewhere. 18,19 Briefly, each cutter was suspended in a vial of either water or porcine vitreous. The vitreous used for the experiments was carefully removed en bloc from porcine eyes enucleated ,12 hours postmortem (Sierra for Medical Science, Whittier, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-five-gauge maximum inflow will be less than 20-gauge maximum inflow [2]. This can be partially compensated for by increasing infusion pressures, but infusion inflow/outflow mismatch is far more likely to happen in a case where the infusion gauge is different from the outflow gauge, e.g.…”
Section: Inflowmentioning
confidence: 99%
“…Recent studies of vitreous dynamics have found that performance, in terms of vitreous removal, differs among 20G, 23G and 25G systems [5], and that infusion and extrusion fluid rates differ among various 25G vitrectomy systems [6]. Currently, angled incision with trocars is a widely-used method for creating sclerotomies in T [7]; however, because of the poor stability of the infusion port, flow of infusion fluid into the anterior chamber during vitrectomy and flow of air into the anterior chamber during fluid-air exchange do occasionally occur.…”
Section: Introductionmentioning
confidence: 99%